2013
DOI: 10.1016/j.newast.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

An asteroseismic study of the Southern Cephei star ALS 3721

Abstract: We present the results of a new investigation aimed to identify the pulsational characteristics of the Southern β Cephei star ALS 3721. Spectroscopic and multicolour photometric data were acquired at the South African Astronomical Observatory (SAAO), South Africa in 2011. Frequency analysis showed that the oscillations of ALS 3721 could be attributed to the two main frequencies with higher significance. Stellar parameters and projected rotational velocity obtained by the spectra were also used to perform photo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 18 publications
2
16
1
Order By: Relevance
“…In Table 1 we show the frequencies, amplitudes, and phases found in both the 2011 and 2014 observations. All of our frequencies are consistent with those found from the Kepler data by Ulusoy et al (2013). Only modes detected with signal to noise S/N > 4.0 are given (Breger et al 1993).…”
Section: Observations and Fourier Analysissupporting
confidence: 88%
See 3 more Smart Citations
“…In Table 1 we show the frequencies, amplitudes, and phases found in both the 2011 and 2014 observations. All of our frequencies are consistent with those found from the Kepler data by Ulusoy et al (2013). Only modes detected with signal to noise S/N > 4.0 are given (Breger et al 1993).…”
Section: Observations and Fourier Analysissupporting
confidence: 88%
“…We first consider the period ratios for the independent modes. Ulusoy et al (2013) claim that the observed period ratio P 1 /P 0 = 0.763 of GSC 03144-595 differs significantly from the expected value for radial first overtone and fundamental modes. However, there is no accepted lower bound for this period ratio, and several double mode pulsators have been observed to have a similar ratio (Poretti et al 2005).…”
Section: Mode Identificationmentioning
confidence: 71%
See 2 more Smart Citations
“…Not like the solar-like stars for which many frequencies are detected, most HADS are observed with only the fundamental and the first overtone modes in general (e.g., Balona et al 2012;Ulusoy et al 2013). As a result, the period variation becomes a very important constraint on the model calculation of these stars.…”
Section: Constraints From the Period Variationmentioning
confidence: 99%